The influence of Surface Roughness on the Lattice thermal Conductivity in Silicon Nanowires - Elham Ahmed Mohammed ,Hawkar Taher Taha (Zanco Journal of Pure and Applied Sciences, 2023)
A modified model is proposed to account for the effects of roughness on lattice thermal conductivity (LTC) in Si nanowires (SiNWs). Depending on the modification of the Debye-Callaway models effects of surface roughness is carried out to predict LTC in SiNWs. Through the process of fitting the calculated curve to that of the reported experimental data, phonon scattering strength from the boundary, Umklapp-normal phonon–phonon processes, electron-phonon and defects were estimated. The phonons scattering through roughness boundaries due to rough nanowires indicates a smaller phonon mean free path compared to that of their diameters. However, the Casimir limit for phonons mean free path particularly in 22nm nanowire diameter found to be due to phonons involved in completely diffused boundary scattering processes, while for other diameters (37, 56, 115) nm, the effects were smaller with values ranging from 0.35 to 0.685. In general, for a given temperature, LTC decreases with the decrease of NWs diameter.